STUDY OF PACKAGE TECHNOLOGY OF HYBRID CORN VUB IN SUKARAJA VILLAGE, DISTRICT SEGINIM, BENGKULU SOUTH REGENCY - miswarti, Miswarti; Yahumri, Yahumri; Hidayat, Taufik; Musaddad, Darkam (JURNAL PANGAN, 2019)
Corn is the second strategic food commodity after rice. The use of superior hybrid corn seeds can increase production and productivity. This study aims to obtain a hybrid corn VUB farming technology package in Bengkulu Province. The assessment was carried out on irrigated paddy fields in Sukaraja Village, Seginim Subdistrict, South Bengkulu Regency from May to August 2018. The RAK design was used with 5 technological package treatments and 5 replications. The data collected consists of growth components, yield components, yields, input and output costs for each treatment. Data was analyzed using variance analysis and DMRT further testing. The feasibility of farming can be seen from the value of compensation for fees or the ratio between revenue and total costs (R/C ratio). The results of analysis of variance on growth components and yield components showed that there was a real effect of treatment on cob weight, number of rows in one cob, and seed weight per ear while on plant height, number of leaves, ear length, number of seeds in 1 row, ear circumference and weight 1000 items have no real effect. P1 technology package (Bima variety 19 URI, Urea 350 kg/ha, SP36 150 kg/ha, KCl 100 kg/ha and without organic matter) with B/C ratio of 2.08, followed by p5 (varieties NK 6172, Urea 300 kg, Phonska 300 kg/ha) gave the highest yield with B/C ratio of 2.04.